Reformasi konsesi HPH: mempertanyakan paradigma "pembalakan lestari" (sustainable logging) - Barr, C. (Yayasan Obor Indonesia, 2003)
Since the mid-1980s, policy discussions aimed at promoting sustainable forest management in Indonesia have focused almost exclusively on reforming the HPH (Hak Pengusahaan Hutan) timber concession system. Policy interventions proposed by the World Bank and other advocates of the “sustainable logging” reform agenda have generally been structured around three key principles – selective cutting, full rent capture, and market-based efficiency. This chapter examines five basic assumptions made by proponents of HPH reform and the policy prescriptions that emerge from them. It argues that HPH reform is unlikely to succeed in reducing Indonesia’s timber harvests to the 'sustainability threshhold' of 25 million m3 per year promoted by the government in the 1990s. The HPH reform agenda fails to address the supply-demand imbalance that exists within Indonesia’s wood processing industries and new technologies that have made previously marginal areas and species commercially viable. It also overlooks the marked decline in the volume of logs generated by concession-holders since the 1980s, as well as a corresponding rise in large-scale forest conversion. Moreover, proponents of the “sustainable logging” paradigm erroneously conclude that sustainable concession management is profitable and that timber companies will have an economic incentive to employ sustainable harvesting practices if they are required to do so.